Conducting a Virtual Research Symposium: Path to Success. (May 2021) - Merritt, Sharon; Kramer, Margaret; Monroe, Martha; Davies, Claire C.
Abstract : Strategies used to change an annual statewide research symposium from a face-to-face experience to a virtual event at a 434-bed Magnet ® redesignated community hospital are described. The program met with success and increased access for attendees. For the 1st time, credited to the virtual format, representatives from all 9 hospitals in the system were able to attend. Feedback following the symposium suggested that participants who live at a distance from the hospital appreciated being able to attend the meeting without traveling, technical issues were promptly resolved, and presenters received positive evaluations.